The Responses of Healthcare Professionals and the Media to the Emergency Mobile Restriction Policies on Social Media - Gustaf Wijaya; Fakhri Zakaria; Rachmah Ida (Nyimak: Journal of Communication, 2022)
Health workers play a vital role during the COVID-19 pandemic, not only in the health facilities but also as a reference in the media. This role arises from the health workers’ accounts on social media amplified by the mass media and public discourse. This study aims to examine the narratives of doctors’ accounts on social media, responding to the emergency period of the Covid-19 pandemic in Indonesia. This study maps and analyzes the narratives of the 10 (ten) doctors’ Twitter accounts in Indonesia during the Emergency Community Activity Restrictions (PPKM) period from 3 July - 23 August 2021 through qualitative content analysis methods. The spread of the Delta variant virus and a significant increase in active cases, death, and bed occupancy rates were recorded during this period. The study shows that each doctor has a different narrative, with the main issues: vaccination, health protocols, health facilities, case data, and government policies related to the pandemic. Some doctors’ narratives are also a form of public pressure on government policies. This study also notes the phenomenon of “twitting to the press” by the mass media because of social restriction.Keywords: Healthcare professional, Twitter, mobility restriction, Covid-19, Indonesia ABSTRAKTenaga kesehatan memiliki peran penting selama masa pandemi COVID-19. Tak hanya menjadi garda depan dalam memutus mata rantai penyebaran virus, namun juga menjadi rujukan informasi bagi masyarakat melalui kemunculannya di media. Peran ini muncul dari keaktifan tenaga medis di media sosial yang diamplifikasi oleh media massa dan kemudian menjadi wacana publik. Tujuan penelitian ini adalah melihat narasi para dokter di sosial media, menyikapi masa darurat pandemic Covid-19 di Indonesia. Penelitian ini memetakan dan menganalisis narasi 10 akun Twitter dokter terpopuler di Indonesia selama periode Pemberlakuan Pembatasan Kegiatan Masyarakat (PPKM) Darurat dari 3 Juli - 23 Agustus 2021 melalui metode analisis isi kualitatif. Periode ini ditandai persebaran virus varian Delta dan kenaikan signifikan jumlah kasus aktif, angka kematian, dan tingkat keterisian tenpat tidur. Hasil penelitian menunjukkan setiap dokter memiliki narasi yang berbeda dalam merespons kebijakan penanganan COVID-19 di media sosial, dengan isu utama meliputi vaksinasi, penerapan protokol kesehatan, fasilitas kesehatan, data kasus, serta pejabat dan kebijakan pemerintah terkait pandemi. Narasi para dokter juga menjadi bentuk tekanan publik kepada kebijakan pemerintah pemerintah. Selain itu, penelitian ini juga mencatat adanya fenomena penerapan twitting to the press oleh media massa sebagai imbas penerapan kebijakan pembatasan sosial.Kata Kunci: Tenaga kesehatan, Twitter, pembatasan mobilitas, Covid-19, Indonesia